Analisis Komparatif Return Saham Dan Volume Perdagangan Saham Sebelum dan Sesudah Harbolnas Pada Perusahaan Dagang Yang Terdaftar Di Bei - Milanda, Devy Putri; Kurniawan, Taufan Adi (Akmenika: Jurnal Akuntansi dan Manajemen, 2020)
The industrial revolution resulted in several industries changing their management in order to survive, one of the industries that was affected quite considerably was the trading industry. This study aims to analyze stock return and Trade Volume Activity (TVA) of trading companies in Indonesia Stock Exchange (IDX) before and after Harbolnas (Hari Belanja Online Nasional) or National Online Shopping Days. The samples are all trading companies that have listed on the IDX in the year 2019. This study use multiple linear regression with a significance level of 5%. The results show there are no significant differences in the abnormal return before and after Harbolnas, and there are no significant differences in the TVA before and after the harbolnas